A Comparison of Improvised and Commercially Available Point-of-Wounding Tourniquets in Simulated Traumatic Amputation with Catastrophic Hemorrhage. Issue 9 (19th May 2020) - Hay-David, Aurélie G C; Herron, Jonathan B T; Thurgood, Andrew; Whittle, Craig; Mahmood, Ansar; Bodger, Owen; Hodgetts, Timothy J; Pallister, Ian
Abstract: Introduction: Catastrophic hemorrhage is the leading cause of preventable trauma deaths in the military and civilian populations. The use of tourniquets by first responders (medical and nonmedically trained) is supported and has the potential to save lives if applied correctly. Aims: We sought to examine the use of 5 tourniquets: 1 improvised and 4 commercially available tourniquets to investigate the time taken to stop simulated bleeding and to secure the device; evidence of rebleeding when the "blood pressure" was restored and to gain qualitative feedback on their application. Materials and Methods: Four commercially available tourniquets (Combat Application Tourniquet [C-A-T], Special Operations Forces Tactical Tourniquet - Wide (SOFTT-W), stretch, wrap, and tuck tourniquet [SWAT-T], and the Tourni-key) and an improvised tourniquet (tie & wooden spoon) were tested on a complex silicone simulation model used to replicate catastrophic hemorrhage from a blast injury with above traumatic knee amputation (SAM 4.1 Trauma Simulation Ltd, UK). To limit the user variability, the same investigator applied each tourniquet and each was tested 3 times. No ethical approval was required to conduct this study. Results: None of the devices took longer than 1 minute to secure. The C-A-T and SOFTT-W were quickest to occlude and secure. Although the Tourni-key took longer statistically, this was unlikely to be a clinically important difference. Compared to the others, the SOFTT-W rebled on 2 out of 3 applications. The improvised tourniquet had an obvious ligature effect because of its narrowness, followed by the Tourni-key. This effect was least evident with the SWAT-T; however, particular care was needed to ensure it was safely secured as it was slippery when wet. Conclusions: All tourniquets tested were effective and swift to apply. The Tourni-key's antipinch card seems helpful in reducing local pain under the windlass. Reinspection for rebleeding is important and should be routinely performed irrespective of the device. The width of the SWAT-T may be beneficial, thereby, reducing the risk of crush injury.